(untitled) - Francesca Romoli (Studi Slavistici, 2018)
On the basis of recent studies aimed at investigating Kirill Turovskij’s preaching, a hypothesis regarding the specificity of his homiletics emerged. If compared with the corpus of instructional sermons dating back to the Kievan period (11th-13th centuries), Turovskij’s homilies stand out for the particular liturgical function that biblical quotations serve within them. In the Slovo na verbnoe voskresenie (Homily for Palm Sunday) and the Slovo o rasslablennom (Homily about the sick man), this function advances primarily an exegetical aim, fulfilled through exegetical devices, while in the Slovo na voznesenie (Homily for Ascension) this very function serves primarily a celebratory aim, fulfilled through dramatizing devices. Recalling patristic models, the homilies seemingly follow – within Turovskij’s homiletics, as well as medieval East Slavic preaching – the Byzantine division between exegetical and festal homilies and the Western one between homily and sermon. The analysis of the Slovo po Pascě (Homily for Low Sunday [Sunday after Easter]) offered in the present article confirms the previous hypothesis. The homily, founded on a chain of biblical, hymnographic, patristic and Byzantine references clearly pointing to its liturgical, patristic and Byzantine sources, closely recovered here, functionally reproduces patristic festal homilies, thus demonstrating the variety of Turovskij’s homiletics.